Sensationalism as an Ethical Issue in Citizen Journalism among Undergraduates of Select Universities in Ogun State, Nigeria - Mufutau Oluwakemi Oriola; Joshua Damilare Agbele (The Open University of Sri Lanka, 2023)
The increasing penetration of the internet and new media technologies has created more avenues for the participation of people, formerly known as media audiences, in the news production process through a practice termed citizen journalism. News about events, people and places break on-the-go as reported by individuals with smartphones, internet connection and social media accounts. However, citizen journalism has promoted sensationalism because sharing of emotion-provoking content is fast becoming a popular culture on social media, thereby posing ethical challenges that call for regulation. This study investigated sensationalism as an ethical issue in citizen journalism among undergraduates in selected universities in Ogun State, Nigeria. It was anchored in social responsibility media theory. The population of this study comprised 53,749 full-time undergraduates of Federal University of Agriculture, Abeokuta; Tai Solarin University of Education, Ijagun; and Babcock University, Ilishan-Remo all in Ogun State, Nigeria. A multistage sampling technique was adopted to select 381 respondents studied using a self-structured questionnaire. Results revealed that a majority of the undergraduates participated in citizen journalism; they mostly shared entertainment content; they were motivated by entertainment, appeal, and controversies in sharing sensational content; but they perceived sensationalism to be ethically wrong. The study recommended media literacy and fact-checking as antidotes to sensationalism in digital media.